L-fucose enhances anti-tumor immunity through modulation of monocyte-derived dendritic cell signaling - Burton, Chase; Lester, Daniel; Lau, Eric (The Journal of immunology (1950), 2023)
Although immunotherapies have emerged as standard of care for severals cancer types, their efficacy remains limited to ~30% of patients. Limited efficacy has in part been attributed to a lack of infiltrating tumor-suppressive immune cells and overabundance of immunosuppressive cell populations. To combat this problem, extensive research efforts have focused on modulating intratumoral T cells to overcome the immunosuppressive tumor microenvironment (TME). While these treatment modalities show promise in preventing intratumoral T cell exhaustion, they fail to provide robust and durable anti-tumor immune responses. For this reason, the targeting of other intratumoral immune subpopulations—particularly dendritic cells (DC)—has become a subject of increased study. The dual activation of anti-tumor and suppression of pro-tumor immune populations is expected to significantly enhance immunotherapeutic outcomes. Recently, our group found that the dietary sugar L-fucose (L-fuc) reduces melanoma tumor growth viaa CD4 +T cell-dependent mechanism. Interestingly, analysis of immune cells in the tumors of L-fuc-treated mice revealed dynamic changes in the DC compartment, predominantly in the monocyte-derived DC subset (moDC). Additionally, myeloid cells treated ± L-fucex vivoexhibited enhanced T cell stimulation, increased neutral fluorescent bait uptake, and altered cytokine production. qPCR-RT analysis revealed that L-fuc affects downstream CD209 signaling, leading to a shift towards an immunostimulatory signature. Together, these data suggest a mechanism to enhance anti-tumor immunity by increasing abundance and immunostimulatory activity of moDCs and supports the use of L-fucose as an immunotherapeutic agent. Supported by funding from Moffitt Cancer Center Skin Cancer Sport Project